2023
DOI: 10.15586/aei.v51i1.700
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A–regulated ciliated cells promote airway epithelium repair in an asthma mouse model

Abstract: Background: Asthma is a chronic inflammatory airway disease that causes damage to and exfo-liation of the airway epithelium. The continuous damage to the airway epithelium in asthma cannot be repaired quickly and generates irreversible damage, repeated attacks, and aggravation. Vitamin A (VA) has multifarious biological functions that include maintaining membrane stability and integrity of the structure and function of epithelial cells. Our research explored the role of VA in repairing the airway epithelium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…According to the research, α-tocopherol, a crucial receptor implicated in the allergic response, was also shown to reduce the expression of FcεRI on the surface of mast cells. The research indicated that α-tocopherol may have a therapeutic benefit for allergic rhinitis, presumably via inhibiting the mast cell PI3K-PKB signaling pathway [161][162][163][164].…”
Section: Tocopherolsmentioning
confidence: 99%
“…According to the research, α-tocopherol, a crucial receptor implicated in the allergic response, was also shown to reduce the expression of FcεRI on the surface of mast cells. The research indicated that α-tocopherol may have a therapeutic benefit for allergic rhinitis, presumably via inhibiting the mast cell PI3K-PKB signaling pathway [161][162][163][164].…”
Section: Tocopherolsmentioning
confidence: 99%